2016
DOI: 10.11144/javeriana.rgyps15-30.gfdm
|View full text |Cite
|
Sign up to set email alerts
|

Gasto farmacéutico en diabetes mellitus en una región de España según el Clinical Risk Group, 2012

Abstract: <p>Se pretende estimar la multimorbilidad asociada con diabetes mellitus tipo 2 y su relación con el gasto farmacéutico, para lo cual se realizó un estudio de corte transversal durante el año 2012. Se identificó a 350 015 individuos diabéticos, a través de códigos clínicos, usando la Clasificación Internacional de Enfermedades y el software 3M Clinical Risk Groups. Todos los pacientes fueron clasificados en cuatro grupos de morbilidad. El primer grupo corresponde al estadio inicial, el segundo grupo incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…The main factor associated to the high cost of management of patients with T2D is the treatment of complications, which account for 71.4% of the total direct costs of T2D [ 18 ]. However, although there are some studies on costs of T2D and its complications at the regional level [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], there is limited evidence of the socioeconomic impact and burden of CKD in patients with T2D in the public health system. Additionally, several studies have shown that healthcare costs dramatically increase with deteriorating renal function, especially in the later stages of the disease, highlighting the need of identifying and mitigating factors that promote CKD progression [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main factor associated to the high cost of management of patients with T2D is the treatment of complications, which account for 71.4% of the total direct costs of T2D [ 18 ]. However, although there are some studies on costs of T2D and its complications at the regional level [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], there is limited evidence of the socioeconomic impact and burden of CKD in patients with T2D in the public health system. Additionally, several studies have shown that healthcare costs dramatically increase with deteriorating renal function, especially in the later stages of the disease, highlighting the need of identifying and mitigating factors that promote CKD progression [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…En concordancia con la evidencia reportada en la literatura acerca del costo de la DM2 se observó que este se incrementa a medida que se eleva el número de comorbilidades (Alvis-Estrada et al, 2016). De hecho, la presencia de comorbilidades suele duplicar el costo en medicamentos o fármacos en la población diabética(Luz María, Enrique, Liliana, Lidia, & Emma Rosa, 2015).…”
Section: Capítulo V Discusiónunclassified